Pengaruh Jenis Pakan yang Berbeda Terhadap Jumlah Telur pada Ikan Beseng-Beseng (Marosatherina ladigesi Ahl, 1936) - Kariyanti Kariyanti; Yeni Savitri Andi Lawi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
The Domestication of broil fish has been successfully carried out. This management effort requires the support of information about the type of feed that is good for the level of gonad maturity to produce a large number of eggs so that it can produce seeds. This study aimed to examine the number of eggs of marinated fish (Marosatherina ladigesi) produced in one spawning by providing different feeds namely Culex sp, Artemia sp., and pellets. This research was conducted for 5 months, starting in April 2019 until August 2019 with a completely randomized experimental design. Natural spawning is carried out in this study by observing differences in spawning systems (mass and individual). The results showed that broilers fed Artemia sp produced the highest number of eggs both in individual and mass spawning, 23-35 items and 83 items, culex sp 19-30 items, and 62 items and pellet feed of 17- 24 items and 43 items respectively. ANOVA test results showed no significant difference between the number of eggs and feed.